1977
DOI: 10.1152/jappl.1977.42.2.139
|View full text |Cite
|
Sign up to set email alerts
|

Causes of high blood O2 affinity of animals living at high altitude

Abstract: We have measured the partial pressure of O2 at 50% saturation (P50) and the concentration of various phosphate compounds in the erythrocytes of the bar-headed goose and the guanaco to establish the cause of the high blood O2 affinity in animals who normally reside at high altitude. The same data were obtained in the blood of two goose species, that live at sea level, and in human blood. At standard conditions (pH 7.4, PCO2 40 Torr, 37 degrees C), P50 was 29.7 Torr in the blood of the bar-headed goose and was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(67 citation statements)
references
References 0 publications
8
57
1
1
Order By: Relevance
“…an decrease in organic phosphate concentration, or c) a decrease in sensitivity to organic phosphates (Petschow et al, 1977).…”
Section: Adaptation To Hypoxia By Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…an decrease in organic phosphate concentration, or c) a decrease in sensitivity to organic phosphates (Petschow et al, 1977).…”
Section: Adaptation To Hypoxia By Animalsmentioning
confidence: 99%
“…The bar headed goose flies over the Himalayas and has remarkably adapted to high altitude hypoxia (Petschow et al, 1977). This bird is native to high altitude and has an Hb-O 2 affinity (standard P 50 =29.7 mmHg) that is much greater than its relatives that are native to sea level (e.g.…”
Section: Adaptation To Hypoxia By Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This species breeds on the high plateaus of central Asia and, remarkably, has been observed flying over the summit of Mt Everest (8850 m) during its fall migration to northeastern India (Swan, 1970). A number of physiological traits increase O 2 uptake, circulation and diffusion to contribute to the remarkable physiological performance of bar-headed geese in hypoxic conditions (Petschow et al, 1977;Perutz, 1983;Jessen et al, 1991;Scott and Milsom, 2007;Scott et al, 2009aScott et al, , b, 2011. Recently, Scott et al (2011) reported variation in cytochrome c oxidase (COX) enzyme kinetics between bar-headed geese and closely related lowland species.…”
Section: Hb Polymorphisms In Deer Micementioning
confidence: 99%
“…The differences in muscle phenotype and O 2 diffusion capacity are part of a suite of evolutionary changes in the O 2 transport pathway of bar-headed geese that improve O 2 flux in hypoxia. One of these alterations, an inherently higher haemoglobin O 2 affinity (Petschow et al 1977), is known to be caused largely by a single amino acid substitution ( Jessen et al 1991;Zhang et al 1996). This improves O 2 transport in hypoxia by enhancing pulmonary O 2 uptake (Scott & Milsom 2007) and assuring better O 2 delivery throughout the body (Faraci et al 1984).…”
Section: (B) Respiration Of Muscle Mitochondria In Geesementioning
confidence: 99%